2011
DOI: 10.2486/indhealth.ms1234
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Distortion in Sketching under Mono and Dual Axes Whole Body Vibration

Abstract: Performance of sedentary activities such as reading and writing, in trains is known to be affected by the vibrations. An experimental study was therefore initiated to investigate the interference perceived in sketching task under low frequency random vibration in both mono and dual axes. Thirty healthy male subjects participated in the study. Random vibration stimuli were excited in various axes in frequency range of 1-20 Hz at magnitudes of 0.4, 0.8 and 1.2 m/s 2 . The task required the subjects to sketch the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This implies that the motion of head is cross coupled for X-axis seat excitation and is more pronounced in backrest posture. Bhiwapurkar et al [30][31] found interference with reading activities due to visual disturbance in backrest posture in fore-aft seat vibration for same vibration magnitude and frequency range. For the forward lean posture, the absence of this second peak implies that the motion of head is small -probably because of the low transmission of X-axis motion of the spine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the motion of head is cross coupled for X-axis seat excitation and is more pronounced in backrest posture. Bhiwapurkar et al [30][31] found interference with reading activities due to visual disturbance in backrest posture in fore-aft seat vibration for same vibration magnitude and frequency range. For the forward lean posture, the absence of this second peak implies that the motion of head is small -probably because of the low transmission of X-axis motion of the spine.…”
Section: Discussionmentioning
confidence: 99%
“…The study is conducted on the vibration simulator developed as a mockup of a railway vehicle, housed in partially soundproof room. 30,31 It consists of a platform of 2 m  2 m size, fabricated from a light aluminum alloy frame with thick steel plates at the top and bottom to which the three exciters pushrods are bolted via ball joints. The platform incorporates a table and chairs with rigid wooden seats securely fixed.…”
Section: Subjects and Subject Posturesmentioning
confidence: 99%